GREENWASHING PRACTICES IN COMPANY MARKETING COMMUNICATIONS (ROUTLEDGE, 2025)
This book explores greenwashing practices in company marketing communications, outlining the different types of greenwashing and recommending strategies for readers to successfully differentiate between greenwashing and green marketing.It reviews the theoretical and practical concepts of greenwashing - focusing on those related to marketing communication and marketing strategy - and highlights the various tools companies utilise to mislead their customers, including green advertising, green packaging, eco-labelling, AI, and social media. Drawing upon specific case study examples, the volume illustrates how and when companies employ these methods and the subsequent impact on the environment, while contrasting these with best practices in ethical, pro-environmental marketing communications. Overall, the book campaigns for increased awareness of greenwashing among stakeholders and outlines a proposal for controlling the implementation of pro-environmental practices in green marketing communication to ensure that consumers are not misled.Assisting readers in easily identifying truly green products, as well as those which have been marketed inaccurately, Greenwashing Practices in Company Marketing Communications will be useful for researchers, academics, and students analysing contemporary marketing communication and its compatibility with the principles of sustainable development.